Examining the Factors that Influence Advertising Avoidance on Social Media: The Case of Vietnam - Vuong, Hoang Phuong (2017)
This research was designed to provide insights into why customers avoid advertising on social media. The current stream of literature is highlighting that advertising value, privacy concern, and perceived relevance of ad are the most common predictors of advertising avoidance on this platform. Therefore, this study examined the relationships between these predictors and advertising avoidance in the context of social media in Vietnam. The study found that perceived entertainment value of ads can influence affective avoidance, behavioral avoidance and cognitive avoidance on Facebook but only behavioral avoidance on Youtube. Secondly, the study found that privacy concern can influence affective avoidance, behavioral avoidance and cognitive avoidance on Youtube but only affective avoidance on Facebook. Thirdly, it was found that perceived relevance of ad has no significant impact on advertising avoidance on any platform. Finally, the data report that Vietnamese social media users tend to avoid ads more on Youtube than on Facebook.